Corpo, cotidiano e sensorialidade : dimensões carnais no cinema contemporâneo - Ribeiro, Leonardo Felipe Vieira (2019)
This work, funded by CAPES, aims to investigate the apoptical of the cinematic experience, its relationship with the body of the spectator, define its measures and its limits at the same time, identifying and reflecting on these physical and corporate exp